Optimalisasi Media Sosial melalui Model AIDA sebagai Sarana Promosi Produk Lokal: Studi Pemberdayaan Tenaga Kerja di Desa Kenep - Ahmad Zaki; Al Fiatul Ula; Erinsa Maharani; Agnes Monalisa; Feri Setyowibowo (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the optimization of social media as a promotional tool for local products through the AIDA (Attention, Interest, Desire, Action) model in the context of workforce empowerment in Kenep Village, Sukoharjo Regency. This research method is descriptive qualitative with a phenomenological approach, this study focuses on understanding the subjective experiences of batik MSME owners in utilizing digital platforms. The results show that although MSME players have succeeded in creating awareness and interest through visual content, but they still face problems in converting this interest into desire and action. Digital marketing training and mentoring are proven to improve technical capacity and digital literacy, but the effectiveness of digital promotion still needs to be improved to optimally drive sales and empower local labor.